[INVITED] Tilted fiber grating mechanical and biochemical sensors. (April 2016) - Guo, Tuan; Liu, Fu; Guan, Bai-Ou; Albert, Jacques
Abstract: The tilted fiber Bragg grating (TFBG) is a new kind of fiber-optic sensor that possesses all the advantages of well-established Bragg grating technology in addition to being able to excite cladding modes resonantly. This device opens up a multitude of opportunities for single-point sensing in hard-to-reach spaces with very controllable cross-sensitivities, absolute and relative measurements of various parameters, and an extreme sensitivity to materials external to the fiber without requiring the fiber to be etched or tapered. Over the past five years, our research group has been developing multimodal fiber-optic sensors based on TFBG in various shapes and forms, always keeping the device itself simple to fabricate and compatible with low-cost manufacturing. This paper presents a brief review of the principle, fabrication, characterization, and implementation of TFBGs, followed by our progress in TFBG sensors for mechanical and biochemical applications, including one-dimensional TFBG vibroscopes, accelerometers and micro-displacement sensors; two-dimensional TFBG vector vibroscopes and vector rotation sensors; reflective TFBG refractometers with in-fiber and fiber-to-fiber configurations; polarimetric and plasmonic TFBG biochemical sensors for in-situ detection of cell, protein and glucose. Highlights: A review of the principle, fabrication, characterization, and implementation of TFBGs have been presented. The progress in TFBG sensing applications with special emphasis on mechanical sensing for structural health monitoring and biochemical sensing for in-situ medical detections have been reviewed. The future development of TFBG sensors with efforts of multidisciplinary collaboration has been discussed for advanced and practical sensing tools using optical fibers.